2019
DOI: 10.3390/math7060529
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Model-Based Multi-Objective Evolutionary Approach to Robust Job Shop Scheduling

Abstract: In the real-world manufacturing system, various uncertain events can occur and disrupt the normal production activities. This paper addresses the multi-objective job shop scheduling problem with random machine breakdowns. As the key of our approach, the robustness of a schedule is considered jointly with the makespan and is defined as expected makespan delay, for which a meta-model is designed by using a data-driven response surface method. Correspondingly, a multi-objective evolutionary algorithm (MOEA) is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Recent studies indicated the effects of robustness in the real time scenario of machine breakdowns. Robustness in the multi-objective optimization with the inclusion of machine breakdowns along with makespan leads to the development of meta-models which, when solved through MOEA, indicates a better convergence and diversity in Pareto solution sets as compared to the slack-based surrogate measures [120,121].…”
Section: Robustness In Job Shop and Industry 40mentioning
confidence: 99%
“…Recent studies indicated the effects of robustness in the real time scenario of machine breakdowns. Robustness in the multi-objective optimization with the inclusion of machine breakdowns along with makespan leads to the development of meta-models which, when solved through MOEA, indicates a better convergence and diversity in Pareto solution sets as compared to the slack-based surrogate measures [120,121].…”
Section: Robustness In Job Shop and Industry 40mentioning
confidence: 99%
“…If it is impossible to determine probability distributions for all random job processing times, other approaches have to be used [11,[22][23][24][25]. In the approach of seeking a robust schedule [22,[26][27][28], a decision-maker looks for a schedule that hedges against the worst-case possible scenario.…”
Section: Approaches To Scheduling Problems With Different Forms Of Unmentioning
confidence: 99%
“…Dynamic scheduling with simulation models can be a way of tackling the problem, as implemented by Turker et al [2]. Evolutionary algorithm approaches are well known, very efficient, and still currently being investigated and developed for the job-shop problem [3], as well as for flexible job-shop scheduling problems [4]. Moreover, the technical constraints and technologies applied in production systems generate different types of blocking situations.…”
Section: Introduction and Targeted Contributionmentioning
confidence: 99%